The impact of learning experience on motivation: A case study of Chinese ethnic minority EFL learners - Ye Xincai (Universitas Pendidikan Indonesia, 2023)
Language motivation research has long been a research focus in the field of second language acquisition. In the past two decades, a large number of motivation studies has been conducted in different social and cultural contexts. Researchers contributed to the explorations of factors that affect learners’ foreign language motivation as well as the relationship between motivation and other aspects of foreign language learning. However, research on Chinese ethnic minority learners’ motivation to learn English is in paucity. Many of the ethnic minority students are proficient in their mother tongue (minority language) and Mandarin (national language), while they are also learning English as a foreign language. The social and cultural contexts to which they are exposed make their English learning complicated. To address the gap, the present study adopted a qualitative research approach in the form of a case study to explore the impact of learning experience on English learning motivation among three Chinese ethnic minority pre-university students. Semi-structured interviews were undertaken with three participants. The findings from the qualitative data revealed that the English learning motivation of the participants was typically examination-directed and greatly influenced by teachers’ teaching style, peers’ attitudes toward English and the overall learning atmosphere in the class. The study provides implications for educational policy making and English instruction in China’s ethnic minority regions.